Performance of Doped Montmorillonite on Photosensitizer Based Natural Dyes Gardenia Jasminoides - Sri Mulijani; Komar Sutriah; Gustini Syahbirin; Shabrina Shabrina (Department of Physics, Sebelas Maret University, 2022)
Dye Sensitized Solar Cell (DSSC) is an electrochemical cell that is able to convert solar energy from light to electrical energy. This technology is needed by the world as a renewable and environment friendly energy. In this study, we evaluate the consideration of modification montmorillonite and Gardenia jasminoides dyes may achieve better performance of DSSC by manufactured DSSC with modified TiO2 semiconductors using montmorillonite (MMT) and Nafion. Performance of DSSC was determined by potentiometer. Atomic force microscope was used to evaluate the characteristic of DSSC. The UV-vis results revealed that the dyes which is extracted from the Gardenia jasminoides content crocin and quercetin compounds. Modification DSSC contains ratio of MMT: nafion (50:50) exhibited highest power conversion efficiency value of 0.8316%. Topography of surface ensured the dyes have occupied surface area and able to promote electron to higher energy. However, MMT and nafion capable to enhance potential of dyes as photosensitizer in DSSC.